NEUTROPHIL TO LYMPHOCYTE RATIO IN EARLY LACTATION AS A PREDICTOR FOR FUTURE EXCLUSION OF DAIRY COWS FROM FARM - Branislava Belić; Marko R. Cincović (Archives of Veterinary Medicine, 2012)
The aim of this study was to determine the threshold value and clinical significance of neutrophils to lymphocytes ratio in cooling the cows in lactation that follows. In routine hematological examination of 114 cows 7-15 days after parturition, the number of neutrophils and lymphocytes and neutrophil to lymphocyte ratio was examined. The marginal value of N: L correlation that best separates the cows that will be cooled from those that will remain in production in the lactation that follows is 1.05. If the N: L ratio at this level is more than 90% probability (specificity 90.32), it can be claimed that the cows will later be cooled from production. If the value of N: L correlation is about 0.65 with 90% confidence it can be assumed that the cows will remain in the herd (sensitivity 90.92). The area under the ROC curve was 0.751, which confirms a significant association between the values of N:L correlation after parturition and cooling the cows from the farm (p ~ 0.01). 72% of cows with the value N:L >1.05 were cooled from production for 12 months, versus 20% of excluded cows with N:L <0.5. The neutrophils to lymphocytes ratio in early lactation is a useful indicator for assessing the risk of cooling the cows from production.